Cerebral palsy in Al-Quseir City, Egypt: prevalence, subtypes, and risk factors - El-Tallawy HN; Farghaly WMA; Shehata GA; Rageh TA; Metwally NA; Badry R; Sayed MAM; Abd El Hamed M; Abd-Elwarth A; Kandil MR (Neuropsychiatric Disease and Treatment, 2014)
Hamdy N El-Tallawy,1 Wafaa MA Farghaly,1 Ghaydaa A Shehata,1 Tarek A Rageh,1 Nabil A Metwally,2 Reda Badry,1 Mohamed AM Sayed,3 Mohamed Abd El Hamed,1 Ahmed Abd-Elwarth,2 Mahmoud R Kandil1 1Department of Neurology, Assiut University, 2Department of Neurology, El Azhr University, Assiut Branch, Assuit, 3Department of Neurology, Sohag University, Solag, Egypt Abstract: Cerebral palsy (CP) is the most frequent cause of motor handicap. The present door-to-door survey was conducted in Al-Quseir City, Egypt, to investigate the epidemiology of CP. All inhabitants were screened by three neurologists. Medical and neurological examinations were performed for all residents and suspected cases of CP were confirmed by meticulous neurological assessment, brain magnetic resonance imaging, electroencephalography, and testing with the Stanford-Binet Intelligence Scale. Forty-six of 12,788 children aged ≤18 years were found to have CP, yielding a childhood prevalence of 3.6 (95% confidence interval 1.48–2.59) per 1,000 live births. Five adults (aged 19–40 years) among 13,056 inhabitants had CP, giving an adult prevalence of 0.4 (95% confidence interval 0.04–0.72) per 1,000. The risk factors for CP identified in this study were premature birth, low birth weight, neonatal jaundice, neonatal seizures, and recurrent abortion in mothers of children with CP. Keywords: cerebral palsy, prevalence, subtypes, risk factors, Egypt